Current State of the Problem of Liver Faciolessis - Turakolov U.N.; Khabibullaev Sh.R. (Scientific Trends, 2024)
According to various estimates, from 2 to 17 million people suffer from fascioliasis in the world, up to 180 million people are at risk of infection. Fascioliasis is classified as a new or re-emerging disease that is common in different latitudes of the world. For these reasons, WHO classifies fascioliasis as an important human disease that deserves international attention. The development cycle of the pathogen and the geographic distribution of the disease are described. The pathogenesis of fascioliasis and the clinical picture of the disease are presented. Diagnosis and differential diagnosis of fascioliasis, treatment are described.
Keywords: Parasitic diseases, fasciola hepatica, liver fascioliasis, helminthiases, fascioliasis.